Le réalisme infime d’Annie Dillard dans Teaching a Stone to Talk - Nathalie Cochoy (Anglophonia)
In Annie Dillard’s Teaching a Stone to Talk, the author’s metaliterary reflection on the intertextual layers of discourse that prove necessary to convey the experience of nature does not so much alienate the text from the world as it creates a new form of realism, based on a coincidence between the infinite malleability of discourse and the constant regeneration of landscape. Far from screening the world from view, Annie Dillard’s interwoven references set the texture of language into relief and immediately reveal the rewarding magic of the most ordinary components of natural life.